1979
DOI: 10.1080/00039896.1979.10667363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex and Dietary Calcium on Intestinal Cadmium Absorption in Rats

Abstract: The influence of sex and dietary calcium on whole-body retention of orally administered 115mCdCl2 has a half-life of 43 days, distinguishing it from 115Cd of half-life 2.3 days was studied in one-year-old control and gonadectomized male and female rats. Gonadectomy was performed at the age of four months. Each of the four experimental groups was divided into three subgroups that were fed rat food with a different calcium content (2.4, 0.7, and 0.3% Ca) throughout the experiment. Regardless of sex and gonadecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…51 Our results are therefore in accordance with those of Kello,et a/. 40 It has previously been shown that kidney cortex and liver are primary targets for Cd, 3 " 6 -20 but Cd can also accumulate to a lesser degree in other soft tissues, as spleen, heart and muscle. 3 -5 ' 11 " 14 -52 Our results confirm this, as all experimental groups had significantly raised Cd levels in the soft tissues, except for muscle of the 5 and 7.5 ppm Cd group and adrenal glands of the 2.5 and 5 ppm Cd group (see Tables I and II).…”
Section: Discussionsupporting
confidence: 95%
“…51 Our results are therefore in accordance with those of Kello,et a/. 40 It has previously been shown that kidney cortex and liver are primary targets for Cd, 3 " 6 -20 but Cd can also accumulate to a lesser degree in other soft tissues, as spleen, heart and muscle. 3 -5 ' 11 " 14 -52 Our results confirm this, as all experimental groups had significantly raised Cd levels in the soft tissues, except for muscle of the 5 and 7.5 ppm Cd group and adrenal glands of the 2.5 and 5 ppm Cd group (see Tables I and II).…”
Section: Discussionsupporting
confidence: 95%
“…Women have also been shown to accumulate more Cd than do men (SUMINO et al 1975). Support for the view that these findings might reflect increased Cd absorption in the female was provided by KELLO et al (1979 a) who observed that whole body retention of Cd by rats 6 days following an oral load was 0.47 ± 0.05% (SE) ofthe dose in females, compared with 0.23 ± 0.06% in normal and 0.40 ± 0.02% in castrated males.…”
Section: Age and Sexmentioning
confidence: 83%
“…This is different from the results obtained with mercury. The difference in whole-body retention of cadmium using control male, control female and gonadectomized mice of both sexes was examined by Kello et al (1979). They reported that the control female group had the highest whole-body retention rate.…”
Section: Discussionmentioning
confidence: 99%